Anterior meatuscopy is more reliable than a sniff test for predicting nasal patency before transnasal endoscopy - Hu, Chi-Tan (Endoscopy International Open, 2015)
Background and study aims: Unsedated transnasal esophago-gastro-duodenoscopy (UT-EGD) has been performed for at least two decades but many techniques related to the procedure have yet to be standardized. We aimed to develope a simple endoscopic method, anterior meatuscopy, to replace the sniff test for selecting the most patent nasal meatus before UT-EGD. We hypothesized that access to the common nasal meatus (CNM), if confirmed by anterior meatuscopy, was a safer route than the inferior (INM) and middle nasal meatuses (MNM) because it would result in reduced epistaxis, nasal pain, and nasal discharge. Patients and methods: We used anterior meatuscopy and an endoscopic meatus scoring scale (EMSS) to identify the optimal meatus for insertion. We evaluated the EMSS frequency distributions for the INM, CNM, and MNM and the reliability of a sniff test in 1,000 consecutive patients. The adverse effects of passing through the CNM versus the INM and MNM, respectively, were compared. Results: In the INM and MNM, the EMSS frequencies were grade I > II > III > 0 whereas those in the CNM were grade II > I > 0 > III. A sniff test was not reliable, given its low sensitivity (63.3 %), specificity (67.3 %), positive predictive value (69.1 %), negative predictive value (61.4 %), and accuracy (65.2 %). Although only 9.2 % of our patients had grade III anterior-to-posterior CNMs, passage through this spacious CNM rather than through the MNM or the INM could significantly reduce epistaxis, nasal pain, and nasal discharge.Conclusions: Anterior meatuscopy is more reliable than a sniff test before UT-EGD. Transnasal endoscopic passage through the endoscopically patent CNM, if detected by anterior meatuscopy, may prevent epistaxis and nasal pain and minimize nasal discharge.